Retrospective analysis of training intensity dstribution based on race pace versus physiological benchmarks in highly trained sprint kayakers - Matzka, M.; Leppich, R.; Sperlich, B.; Zinner, C. (Sports Medicine - Open, 2022)
Background: Research results on the training intensity distribution (TID) in endurance athletes are equivocal. This non-uniformity appears to be partially founded in the different quantification methods that are implemented. So far, TID research has solely focused on sports involving the lower-body muscles as prime movers (e.g. running). Sprint kayaking imposes high demands on the upper-body endurance capacity of the athlete. As there are structural and physiological differences between upper- and lower-body musculature, TID in kayaking should be different to lower-body dominant sports. Therefore, we aimed to compare the training intensity distribution during an 8-wk macrocycle in a group of highly trained sprint kayakers employing three different methods of training intensity quantification. Methods: Heart rate (HR) and velocity during on-water training of nine highly trained German sprint kayakers were recorded during the final 8 weeks of a competition period leading to the national championships. The fractional analysis of TID was based on three zones (Z) derived from either HR (TIDBla-HR) or velocity (TIDBla-V) based on blood lactate (Bla) concentrations (Z1 = 2.5 mmol L-1 Bla, Z2 = 2.5-4.0 mmol L-1 Bla, Z3 = 4.0 mmol L-1 Bla) of an incremental test or the 1000-m race pace (TIDRace): Z1 = 85% of race pace, Z2 = 86-95% and Z3 = 95%. Results: TIDBla-V (Z1: 68%, Z2: 14%, Z3: 18%) differed from TIDBla-HR (Z1: 91%, Z2: 6%, Z3: 3%) in each zone (all p < 0.01). TIDRace (Z1: 73%, Z2: 20%, Z3: 7%) differed to Z3 in TIDBla-V (p < 0.01) and all three TIDBla-HR zones (all p < 0.01). Individual analysis revealed ranges of Z1, Z2, Z3 fractions for TIDBla-HR of 85-98%, 2-11% and 0.1-6%. For TIDBla-V, the individual ranges were 41-82% (Z1), 6-30% (Z2) and 8-30% (Z3) and for TIDRace 64-81% (Z1), 14-29% (Z2) and 4-10% (Z3). Conclusion: The results show that the method of training intensity quantification substantially affects the fraction of TID in well-trained sprint kayakers. TIDRace determination shows low interindividual variation compared to the physiologically based TIDBla-HR and TIDBla-V. Depending on the aim of the analysis TIDRace, TIDBla-HR and TIDBla-V have advantages as well as drawbacks and may be implemented in conjunction to maximize adaptation.